The Effectiveness of Sand Tray Therapy in Addiction Counseling as an Intervention in Increasing Treatment Motivation of Recovering Adolescents - Muhammad Syakirin Md Salleh; Ku Suhaila Ku Johari; Mohamad Isa Amat; Zuraidah Ayob (RedwhitePress)
Addiction counseling is one of the critical components in substance use disorders (SUD) as it helps individuals to identify problematic behaviours and change them into positive. Sand tray therapy is an approach in the counselling process in order to explore the problems and issues of the client. The purpose of this study is to measure the effectiveness of the sandtray therapy in increasing the motivation towards change among adolescent substance abuse at Cure and Care (CnC), the residential substance abuse treatment facility supervised by the National Anti Drug Agency (AADK) in District of Kota Bharu, state of Kelantan.This was a quantitative research using repeated-measure on pre and post test among 32 adolescent substance abuse. This study employed The Stage of Change and Treatment Eagerness Scale (SOCRATES). Result shows that sandtray therapy approach has been found to increase the motivation among adolescent subtance abuse to change. The discussion of findings, study implication and future direction are also included.